Starting continuous improvement; creating a common understanding of stroke care delivery in a general hospital - Are Fjermeros; Geir Vegard Berg; Halvor Holtskog; Jos Benders (BMC, 2024)
Abstract Background Continuous improvement is based on fostering practitioners' suggestions to modify their own work processes This improvement strategy is widely applied in healthcare but difficult to maintain. The cross-disciplinary nature of many care processes constitutes an extra impediment. Methods The study had an explorative design with a qualitative single-case approach. The case presents a project to improve the treatment of patients with thrombotic stroke. Data was obtained via hands on involvement, documents, observations, and interviews with participants in a cross-functional improvement group. A thematic analysis method was employed. Results Through learning how tasks were carried out in other disciplines, the participants developed a common understanding of why it took so long to provide treatment to stroke patients. These insights were used to implement practical changes, leading to immediate improvements in stroke care delivery. The results were fed back so that successes became visible. Participants' understandings of the local context enabled them to convince peers of the rationale of changes, setting in motion a permanent improvement structure. The participants considered that mapping and then assessing the entire workflow across disciplines were relevant methods for improving the quality of patient care. Conclusion Starting an improvement project in a cross disciplinary environment requires deep engagement on the part of professionals. A quintessential prerequisite is therefore the realization that the quality of care depends on cross-disciplinary cooperation. A facilitated learning arena needs to (1) create insights into each other's colleagues' tasks and process interdependencies, (2) increase understanding of how the distribution of tasks among specialist units affects the quality of care, and (3) frequently report and provide feedback on results to keep the process going.